The role of histologic subtype, p16(INK4a) expression, and presence of human papillomavirus DNA in penile squamous cell carcinoma - Steinestel, Julie; Al Ghazal, Andreas; Arndt, Annette; Schnoeller, Thomas J; Schrader, Andres J; Moeller, Peter; Steinestel, Konrad (BMC cancer, 2015)
Up to 50% of penile squamous cell carcinomas (pSCC) develop in the context of high-risk human papillomavirus (HR-HPV) infection. Most of these tumours have been reported to show basaloid differentiation and overexpression of tumour suppressor protein p16(INK4a). Whether HPV-triggered carcinogenesis in pSCC has an impact on tumour aggressiveness, however, is still subject to research. In tissue specimens from 58 patients with surgically treated pSCC between 1995 and 2012, we performed p16(INK4a) immunohistochemistry and DNA extraction followed by HPV subtyping using a PCR-based approach. The results were correlated with histopathological and clinical parameters. 90.4% of tumours were of conventional (keratinizing) subtype. HR-HPV DNA was detected in 29.3%, and a variety of p16(INK4a) staining patterns was observed in 58.6% of samples regardless of histologic subtype. Sensitivity of basaloid subtype to predict HR-HPV positivity was poor (11.8%). In contrast, sensitivity and specificity of p16(INK4a) staining to predict presence of HR-HPV DNA was 100% and 57%, respectively. By focussing on those samples with intense nuclear staining pattern for p16(INK4a), specificity could be improved to 83%. Both expression of p16(INK4a) and presence of HR-HPV DNA, but not histologic grade, were inversely associated with pSCC tumour invasion (p = 0.01, p = 0.03, and p = 0.71). However, none of these correlated with nodal involvement or distant metastasis. In contrast to pathological tumour stage, the HR-HPV status, histologic grade, and p16(INK4a) positivity failed to predict cancer-specific survival. Our results confirm intense nuclear positivity for p16(INK4a), rather than histologic subtype, as a good predictor for presence of HR-HPV DNA in pSCC. HR-HPV / p16(INK4a) positivity, independent of histological tumour grade, indicates a less aggressive local behaviour; however, its value as an independent prognostic indicator remains to be determined. Since local invasion can be judged without p16(INK4a)/HPV-detection on microscopic evaluation, our study argues against routine testing in the setting of pSCC.